2022
DOI: 10.1021/acsami.1c24363
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Effect of Sulfur Incorporation into Tungsten Diphosphide for Improved Hydrogen Evolution Reaction

Abstract: Exploring the highly active and stable nonprecious metal electrocatalysts is particularly important for the advancement of water electrolysis, whereas it remains a challenge to efficiently improve the intrinsic electrocatalytic activity. Herein, we reasonably constructed a self-supporting nanosheet array material with sulfur incorporated into WP2. Because of the tunability of electronic configuration and the formation of partial metal phase sulfides, the optimized catalyst exhibits a low overpotential of 115 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…For Mo/Cu, the calculated Δ G H* value is 0.45 eV, which is too weak for hydrogen adsorption. In contrast, NiMo/Cu has a Δ G H* very close to 0, which is 0.07 eV, and has the lowest reaction energy barrier . In addition, we further calculated the total density of states (TDOS) for Ni/Cu, Mo/Cu, and NiMo/Cu, with the results illustrated in Figure c–e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For Mo/Cu, the calculated Δ G H* value is 0.45 eV, which is too weak for hydrogen adsorption. In contrast, NiMo/Cu has a Δ G H* very close to 0, which is 0.07 eV, and has the lowest reaction energy barrier . In addition, we further calculated the total density of states (TDOS) for Ni/Cu, Mo/Cu, and NiMo/Cu, with the results illustrated in Figure c–e.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, NiMo/Cu has a ΔG H* very close to 0, which is 0.07 eV, and has the lowest reaction energy barrier. 34 In addition, we further calculated the total density of states (TDOS) for Ni/Cu, Mo/Cu, and NiMo/Cu, with the results illustrated in Figure 7c−e. It can be deduced that the TDOSs also prove that the optimal HER activity was possessed by NiMo/Cu, since the d-band center of Mo/Cu (−1.721 V) is the farthest from the Fermi energy level with the adsorption of H* being too weak and the d-band center of Ni/Cu (−1.422 V) is the nearest from the Fermi energy level with adsorption of H* being too strong.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…To date, transition metal-based OER catalysts have been extensively applied, including transition metal hydroxides, sulfides, phosphides, and transition metal/nitrogen-doped carbon materials . Past research studies have shown that FeNi oxyhydroxide is located at the top of the Sabatier-type volcano plots, and FeNi LDH tends to be among the most active OER electrocatalysts due to the interaction between Fe and Ni bimetals .…”
Section: Introductionmentioning
confidence: 99%
“…20 Since water electrolysis was first studied by Troostwijk and Diemann in 1789, it has been extensively investigated by researchers around the world. 21–23 Alternatively, electrolyzing water is a desirable method to yield H 2 with high purity and efficiency. 24–26 Accordingly, efficient and stable electrocatalysts are urgently developed and used for the HER.…”
Section: Introductionmentioning
confidence: 99%